COVID-19 and public support for the euro - Felix Roth; Lars Jonung; Aisada Most (Lund University, School of Economics and Management, Department of Economics, 2023)
The COVID-19 pandemic had disastrous effects on health and economic activity worldwide, including in the Euro Area. The application of mandatory lockdowns contributed to a sharp fall in production and a rise in unemployment, inducing an expansionary fiscal and monetary response. Using a uniquely large macro database, this paper examines the effects of the pandemic and the ensuing economic policies on public support for the common currency, the euro, as measured by the Eurobarometersurvey. It findsthat public support for the euro reached historically high levels in a majority of the 19 Euro Area member states in the midst of the pandemic. This finding suggests that the expansionary fiscal policies initiated at the EU level significantly contributed to this outcome, while the monetary measures taken by the European Central Bank did not have a similar effect.
Keywords: C23; E24; E42; E52; E62; I18; 330; COVID-19; lockdowns; support for the euro; unemployment; inflation; monetary policies; fiscal policies; EU